2017
DOI: 10.1007/s00380-017-1028-x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine arteriogenesis based on vasa vasorum in a novel semi-acute occlusion model using high-resolution imaging

Abstract: Bridging collaterals (BC) develop in several chronic total artery occlusion diseases, and can prevent extensive myocardial necrosis. Yet, their origin, growth process, and histo-morphology are still unclear. Since vasa vasorum (VV) may take part in collateralization, we hypothesized that VV are the basis for BCs. To comprehensively investigate this arteriogenesis process, we used high-resolution imaging, including corrosion casts, post-mortem angiography with stereoscopy, micro-CT, and immunohistology, in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…In previous studies (2-4), multiple vascular channels which run distinctly outside of the expected lumen of occluded arteries were generally recognized as bridging collaterals developed from VV. In the process of maturation, the adventitial collaterals grow both in width and length and therefore develop a typical corkscrew-like or beadlike morphology (5,6), which are not consistent with the angiography presented by the authors.…”
contrasting
confidence: 81%
“…In previous studies (2-4), multiple vascular channels which run distinctly outside of the expected lumen of occluded arteries were generally recognized as bridging collaterals developed from VV. In the process of maturation, the adventitial collaterals grow both in width and length and therefore develop a typical corkscrew-like or beadlike morphology (5,6), which are not consistent with the angiography presented by the authors.…”
contrasting
confidence: 81%
“…e aneurysm rupture, SAH, affects the aforementioned peculiar way of nourishing the cerebral vasculature. Studies have reported that SAH induces severe subarachnoid vessel wall injury, including intimal edema and thickening, disruption of the internal elastic lamina, media thickening, smooth muscle cell necrosis, intramural hematoma, and VV recruitment in human cadavers [23] and animal models. [49] Furthermore, in SAH, the elevated intracranial pressure reduces oxygen pressure by diffusion from both the lumen inside and outside VVs, which further aggravates delayed vasospasm.…”
Section: Cerebral Aneurysm and Subarachnoid Hemorrhage (Sah)mentioning
confidence: 99%
“…A study reported that when porcine coronary arteries were gradually occluded, anastomoses between VVs running in the longitudinal direction develop and constitute fully functional collaterals in a concise timeline, which can be as short as a week. [23] In clinical situations, some authors reported that the collaterals formed by VVs and the occluded internal carotid artery (ICA) in cases with a giant aneurysm in the cavernous sinus segment, [46] with atherosclerotic ICA occlusion adjacent to the carotid bifurcation, [11,26,61] and with atherosclerotic basilar artery occlusion restored its distal flow through VV collaterals. We assume that these VV collaterals usually develop in extracranial segments or proximal parts of the internal carotid or vertebral arteries, depending on their physiological distribution.…”
Section: Collateral Channelsmentioning
confidence: 99%